Conditional terms in semantic programming - Goncharov, S. S. (Siberian mathematical journal, 2017)
For constructing an enrichment of the language with restricted quantifiers, we extend the construction of conditional terms. We show that the so-obtained extension of the language of formulas with restricted quantifiers over structures with hereditary finite lists is a conservative enrichment.